2017
DOI: 10.3389/fphar.2017.00933
|View full text |Cite
|
Sign up to set email alerts
|

CP-25, a Novel Anti-inflammatory and Immunomodulatory Drug, Inhibits the Functions of Activated Human B Cells through Regulating BAFF and TNF-alpha Signaling and Comparative Efficacy with Biological Agents

Abstract: Paeoniflorin-6′-O-benzene sulfonate (code: CP-25) was the chemistry structural modifications of Paeoniflorin (Pae). CP-25 inhibited B cells proliferation stimulated by B cell activating factor belonging to the TNF family (BAFF) or Tumor necrosis factor alpha (TNF-alpha). CP-25, Rituximab and Etanercept reduced the percentage and numbers of CD19+ B cells, CD19+CD20+ B cells, CD19+CD27+ B cells and CD19+CD20+CD27+ B cells induced by BAFF or TNF-alpha. There was significant difference between CP-25 and Rituximab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…The increase in the number of circulating B cells may be owing to the continuous activation of B cells (Lindenau et al, 2003). Previous studies by our team have found that abnormal activation of B cells does exist in RA patients (Zhang et al, 2017). This study showed that the percentage of CD19 + total B cells, CD19 + CD27 + memory B cells, and CD19 − CD27 + CD138 + plasma B cells, the levels of TNF-a, BAFF, laboratory parameters, and clinical indicators of RA patients all decreased after etanercept treatment.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The increase in the number of circulating B cells may be owing to the continuous activation of B cells (Lindenau et al, 2003). Previous studies by our team have found that abnormal activation of B cells does exist in RA patients (Zhang et al, 2017). This study showed that the percentage of CD19 + total B cells, CD19 + CD27 + memory B cells, and CD19 − CD27 + CD138 + plasma B cells, the levels of TNF-a, BAFF, laboratory parameters, and clinical indicators of RA patients all decreased after etanercept treatment.…”
Section: Discussionmentioning
confidence: 86%
“…Further, B cells produce receptor activator of NF-kB ligand (RANKL) near the osteoclast precursors and promote bone destruction in a RANKL dependent way within synovium ectopic lymphoid structures (Sun et al, 2018). A previous study of our research group proved that abnormal activation of B cells participates in the pathological process of RA (Zhang et al, 2017). B cell activating factor (BAFF) belongs to the tumor necrosis factor superfamily, which is a crucial factor for B cell survival and maturation (Shin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found that CP-25 inhibited activated human B cells by regulating B-cell activating factor and TNF-α signaling. Compared with the effects of rituximab and etanercept, CP-25 showed modest activity, suggesting that CP-25 may provide a promising approach to the soft regulation of inflammation ( Zhang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…CP-25 is a derivative of the natural product paeoniflorin 130 , which is able to inhibit B-cell proliferation in a similar manner to rituximab (CD20 B-cell targeting antibody) and etanercept (TNF receptor chimera) and also downregulate the expression of BAFF-R on B cells. The mechanism of these effects is not reported 131 . It will be interesting to note the progression of this compound and ones with a similar mode of action.…”
Section: B Cell–activating Factor and Tumour Necrosis Factor Alpha Rementioning
confidence: 98%